Diversidade de Borboletas Frugívoras (Lepidoptera: Nymphalidae) na Reserva Particular do Patrimônio Natural "KIagesi" (RPPN) no Município de Santo Antônio do Tauá, PA - Torres, Lorena Chagas (Museu Paraense Emílio Goeldi, 2023)
The increasing anthropogenic alteration of habitats has led to a reduction of the butterfly fauna in Belém and its surroundings, making it necessary to study the diversity of the remaining species in order to promote their preservation. Butterflies are important indicators for assessing environmental impacts. The frugivorous species of the Nymphalidae family are responsible, in general, for about 40% of butterfly species richness in Neotropical forested environments. The present work is a contribution to the knowledge of butterfly diversity in the Klagesi Reserve (RPPN) in Santo Antônio do Tauá, PA, an area of 23 ha of forest. Butterflies were captured in traps suspended at variable heights from 1.5 m to 5.0 m, with fermented fruit baits. After collection, individuals were killed using bottles containing ethyl acetate for small species or with acetone injection in the thorax for larger species. They were then properly mounted with entomological pins and dried in an oven. Identification was done using bibliographic materials from the reserve. To date, 54 species of frugivorous Nymphalidae have been recorded, distributed in 4 subfamilies and 25 genera. Taxonomic and biological information on each species was put into a database, using as a base the catalog of Neotropical butterflies by Lamas (2004) and other treatises. The richness of the species, despite the use of a single collection technique, shows the importance for environmental preservation of RPPNs, even those of smaller size. Comparisons with the faunas of frugivorous butterflies from Belém and the Caxiuanã National Forest indicated differences in the most common species. Taking advantage of the rainy season, new traps were placed at different points in the reserve and it is hoped to further increase the number of recorded species of frugivorous butterflies.